Service Performance of Transjakarta City Bus Public Transportation System Corridor 1, 3 And 9 - Siti Kagiarin; Ruchyat Deni Djakapermana; Arif Wicaksono (Publikasi Indonesia, 2024)
Transjakarta has implemented smart mobility i.e. the information technology (IT) and artificial intelligence (AI), and therefore this study focuses to discuss the performance of its smart mobility practices. The measurement of smart mobility performance in Transjakarta was carried out using in-depth analysis for each of variables such as load factor, travel speed, headway, frequency, waiting time, service time and circulation time. The perception of Transjakarta passangers was collected using distributed questionnaires in online surveys to obtain public aspirations for smart mobility service performance improvement. A total of 434 respondents filled the questionnaires which were distributed randomly in three bus corridors. As a result, 261 resondents (60,14%) stated that Passenger Information System (PIS) has given accurate information about the schedule of Transjakarta, while 173 respondents (39,86%) stated otherwise. In conclusion, the service performance in Transjakarta Corridor 1,3, and 9 can be categorized as medium when compared to official minimum service standard.